Phase Equilibria and Phase Diagrams for the Aqueous Ternary System Containing Sodium, Chloride, and Metaborate Ions at 288.15 and 308.15 K and 0.1 MPa - Wanjing Cui; Hongfang Hou; Jiayin Hu; Yafei Guo; Tianlong Deng (Journal of Chemistry)
Salt-water phase diagram of the ternary system (NaCl + NaBO2 + H2O) is significant in separate boron resources from brine. Solubilities and physicochemical properties bifurcated to density and refractive index for the ternary system at 288.15 and 308.15 K and 0.1 MPa were investigated experimentally by means of isothermal dissolution. According to the experimental data, the phase diagrams for this system at two temperatures were constructed and their physicochemical properties were drawn. There both contain two invariant points, three univariant isotherm dissolution curves, and three crystallization regions corresponding to sodium metaborate tetrahydrate (NaBO2·4H2O, Smt), double salt teepleite (NaCl·NaBO2·2H2O, Te), and halite (NaCl, Ha) for (NaCl + NaBO2 + H2O). At the invariant points of this ternary system, the coexisting solid phases are both for (Smt + Te) and (Te + Ha), respectively. It was found that the double salt of teepleite was incongruent at 288.15 K and then transformed into congruent at 308.15 K. Comparing the phase diagrams at 288.15 and 308.15 K, it reveals that the area of the crystallization region of NaBO2·4H2O decreased with the increase of temperature obviously, while the area of NaCl·NaBO2·2H2O increased sharply and that of NaCl increased lightly. The refractive indices and densities of the system at two temperatures are similarly increased firstly and then decreased with the increase of NaCl concentration in the solution and attain extreme points at both invariant points. Besides, the calculated values of densities and refractive indices utilizing the empirical equations are in accordance with the experimental data at 288.15 and 308.15 K.